3-Methyoxy Flavones: The Potential Antiviral Agents From Citrus Recticulata, Blanco - Saxena, V.K.; Shrivastava, Preeti (Asian Journal of Chemistry, 2010)
Phytochemical study of the fruits of Citrus reticulata Blanco afforded kaempferide trimethyl ether 1 and quercetin 3,7,3´,4´-tetramethyl ether 2 which were characterised by various chemical degradations and spectral studies.